Methods in Molecular Medicine - Tutar, Yusuf (IntechOpen, 2021)
Treatment risk and response to therapy prediction can be forecasted through early diagnosis, which improves prognosis reliability and effectiveness of therapies. This book covers contemporary advances in molecular markers, disease-causing variants, retroelements, and the basis of distinct diseases.